Safety and immunogenicity of chromatographically purified Vero cell rabies vaccine for intradermal pre- and post-exposure rabies prophylaxis. (December 2014) - Tantawichien, Terapong; Sibunruang, Suda; Tantawichien, Thanphet; Angsanakul, Jaruboot; Benjavongkulchai, Maneerat; Limsuwan, Kornvika; Udomchaisakul, Piyada; Khomvilai, Sumana; Sitprija, Visith
<x xml:space="preserve">Abstract</x> Improved rabies pre- and post-exposure prophylaxis (PrEP and PEP) in developing countries uses an economic multi-site intradermal vaccination. Aim: To evaluate immunogenicity of chromatographically purified Vero cell vaccine (CPRV) for intradermal PrEP and PEP. Method: The subjects received conventional PrEP with CPRV or PVRV in PrEP study or received intradermal PEP with CPRV or PVRV and rabies immunoglobulin in PEP study. Result: All subjects who received PrEP with CPRV had protective neutralizing antibody (Nab) titers (≥0.5 IU/ml) 14 days after completing vaccination. In PEP study, Nab titers in the CPRV groups reached ≥ 0.5 IU/ml in all subjects by day 14 through day 90 after vaccination. The geometric mean titers of Nab in the CPRV groups had significantly higher titers than the PVRV group on day 14 through day 365 (p < 0.05). No serious adverse reactions were observed. Conclusions: CPRV is safe and immunogenic when given for intradermal PrEP and PEP.